Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Handphone Merek Oppo Pada Toko Pelangi Ponsel di Tabanan - Rahayu, Ni Desak Made Putri; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research aims to determine the influence of brand image and price, partially and simultaneously, on purchasing decisions for Oppo cellphones at the Pelangi Ponsel Store in Tabanan. This type of research is causal research with a quantitative approach. The population used is consumers who have purchased and used Oppo cellphones in the city of Tabanan. The sampling used was a purposive sampling technique, so the sample used was 100 respondents. The type of data used is quantitative data, and the data sources used are primary data sources and secondary data. Data collection methods use questionnaires, documentation, and observation. Data processing uses the help of the Statistical Package for The Social Science (SPSS) version 25 program. The data analysis technique used is multiple linear regression analysis with partial (t-test) and simultaneous (F-test) hypothesis testing. The results of this research show that (1) brand image has a positive and significant influence on the decision to purchase Oppo cellphones at the Pelangi Ponsel Store in Tabanan, (2) price has a positive and significant influence on the decision to purchase Oppo cellphones at the Pelangi Ponsel Store in Tabanan, and (3) brand image and price simultaneously have a positive and significant effect on the decision to purchase an Oppo cellphone at the Pelangi Ponsel Store in Tabanan.